Analysis of Workplace Violance at Accredited Hospitals in Riau Province - Dilgu Meri; Fitra Mayenti (STIKep PPNI Jawa Barat, 2022)
Aims: Hospital violence against health care providers, particularly nurses, is a significant problem in every healthcare setting in the world. The purpose of this study was to analyze workplace violence among nurses at an Accredited Hospital in Pekanbaru city. Methods: The type of research used in this study is quantitative research with an analytic descriptive approach. The sample in this study were the nurses in RSUD X and RS Y, amounting to 50 people. In this study using a questionnaire as a data collection tool. The questionnaire was adopted from the Texas Center for Nursing workforce studies regarding workplace violation against nurses survey. Results: The results of research at RSUD X found that 100% of respondents stated that there was no evaluation of the effectiveness of the impact of violence at work policies, 92% of respondents said they did not know about policy changes based on evaluations of violence prevention programs in the workplace, 100% of respondents stated that violence training in the workplace work is not provided, the results of research at the RS Y found that of the 25 respondents as much as 40% of respondents stated the availability of verbal violence policies from patients or visitors, 48% of respondents stated that the policy of preventing violence in the workplace was needed related to incident reporting, 36% of respondents stated that appropriate technical training is needed to reduce conflict, 72% of respondents 28 stated the availability of follow-up support such as counseling for nurses who experience verbal / physical violence. Conclusions: The results of this study can be used as one of the considerations in efforts to overcome and prevent work stress in nurses and as information for management regarding problems faced by nurses at work.